The Role of Telemedicine in Managing Patients During the COVID-19 Pandemic: A Systematic Review of Clinical Applications and Challenges: A Literature Review - NAUVAL LAZUARDI PRATAMA (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2026)
The COVID-19 pandemic has accelerated the adoption of telemedicine, improving access to remote healthcare, chronic disease management, and health education. However, its effectiveness varies, particularly for conditions requiring physical assessment. This systematic review evaluates the role of telemedicine during the pandemic, its benefits, challenges, and future implications. Telemedicine has proven effective in consultations and patient education but remains limited in physical examinations. Hybrid healthcare models integrating telemedicine and in-person visits are recommended to ensure sustainable healthcare delivery post-pandemic.